Biodiesel Potentials of Waste Cooking Oil (WCO): Production, Content of Fuel Properties, and Effects on Engine Performance - Suardi Suardi; Doddy Suanggana; Basri Said (International Journal of Marine Engineering Innovation and Research, 2023)
The potential for biodiesel to become the main fuel in the future seems to be getting brighter with the enactment of government policies related to the implementation of the Euro 4 standard. In addition, the government has also launched de-carbonization to reduce the greenhouse effect by referring to the International Maritime Organization (IMO) plan which sets a target of reducing world carbon emissions by 40% by 2030 and 70% by 2050. To answer this challenge, this research aims to find out the bio-diesel production process by utilizing waste cooking oil (WCO), the next step is whether the biodiesel produced has content properties that are following the quality standards set by the government, the final step is that the bio-diesel is tested on a test engine to know the value of the engine performance produced. In this research two types of methods are used to solve the problem, the first is the transesterification method, which is a method commonly used in the process of making biodiesel, this method utilizes a catalyst to separate pure biodiesel from glycerol, in this research using methanol and NaOH catalysts. The second method is the experimental method, which is testing biodiesel directly on the engine so that the resulting engine performance values including power, torque, and SFC can be known. The test obtained results in the form of content of fuel properties still included in government standards which include Density, Viscosity, Flash Point, Pour Point, and Cetane Number. The best torque value is in the B15 fuel variation at engine speeds of 1400 RPM and 1600 RPM, for the best effective power value results in the B15 fuel variation using engine speed of 1600 RPM, and the best specific fuel consumption value in the B15 fuel variation at 1000 RPM engine speed. So it can be concluded that mixing coconut cooking oil with pure cooking oil into biodiesel can be used as an alternative fuel and has a good impact on diesel engine performance.